Activating and inactivating mutations of the human, rat, equine and eel luteinizing hormone/ chorionic gonadotropin receptors (LH/CGRs) - Kwan-Sik Min; Munkhzaya Byambaragchaa; Seung-Hee Choi; Hyo-Eun Joo; Sang-Gwon Kim; Yean-Ji Kim; Gyeong-Eun Park (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Mutations in the luteinizing hormone/chorionic gonadotropin receptors (LH/CGRs), representatives of the G protein-coupled receptor family, have been rapidly identified over the last 20 years. This review aims to compare and analyze the data reported the activating and inactivating mutations of the LH/CGRs between human, rat, equine and fish, specifically (Japanese eel Anguilla japonica). Insights obtained through detailed study of these naturally-occurring mutations provide a further update of structure-function relationship of these receptors. Specifically, we present a variety of data on eel LH/CGR. These results provide important information about LH/CGR function in fish and the regulation of mutations of the highly conserved amino acids in glycoprotein hormone receptors.